2014
DOI: 10.3389/fncel.2014.00297
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identity of axonal sodium channels in human cortical pyramidal cells

Abstract: Studies in rodents revealed that selective accumulation of Na+ channel subtypes at the axon initial segment (AIS) determines action potential (AP) initiation and backpropagation in cortical pyramidal cells (PCs); however, in human cortex, the molecular identity of Na+ channels distributed at PC axons, including the AIS and the nodes of Ranvier, remains unclear. We performed immunostaining experiments in human cortical tissues removed surgically to cure brain diseases. We found strong immunosignals of Na+ chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 93 publications
11
89
0
Order By: Relevance
“…In both PV and SST interneurons, Na v 1.6 channels were found in the distal part of the AIS, whereas Na v 1.2 channels were found in the proximal part of the AIS only in SST-positive INs [60] . A recent study showed that, in human cortical pyramidal cells, the pattern of Na + channel distribution is similar to that in rodents [64] . The primary difference was a clustering of Na v 1.2 channel in some nodes of Ranvier in addition to the Na v 1.6 channels.…”
Section: Na + Channelsmentioning
confidence: 77%
See 1 more Smart Citation
“…In both PV and SST interneurons, Na v 1.6 channels were found in the distal part of the AIS, whereas Na v 1.2 channels were found in the proximal part of the AIS only in SST-positive INs [60] . A recent study showed that, in human cortical pyramidal cells, the pattern of Na + channel distribution is similar to that in rodents [64] . The primary difference was a clustering of Na v 1.2 channel in some nodes of Ranvier in addition to the Na v 1.6 channels.…”
Section: Na + Channelsmentioning
confidence: 77%
“…TRPM2 channels are thought to be activated by reactive oxygen species (ROS), nitric oxide (NO), and ADP-ribose (ADPR) [89] . TRPM7 channels can be activated through low extracellular divalent cations, ROS, and pH changes [64] . All of the above are present in neuronal injury areas.…”
Section: + Overloadmentioning
confidence: 99%
“…In addition, and correlating with the predominant localization of Nav1.1 in the AIS of GABAergic neurons (Ogiwara et al, 2007; Lorincz and Nusser, 2008; Catterall et al, 2010; Tian et al, 2014), the loss of proper localization and function of Nav1.1 is considered to be a factor for the onset of epilepsy caused by a disruption of the inhibitory balance in the brain (Catterall et al, 2010). …”
Section: Compartmentalized Distribution Of Vgcs In Axonsmentioning
confidence: 99%
“…SCN2A stands out from other ASD-associated genes in several ways. First, while most ASD-associated genes are related to either chromatin regulation or synapse structure (2), Na V 1.2 channels are primarily expressed in the axon (610). Second, along with de novo PTVs, an excess of de novo missense mutations is also observed in SCN2A , a pattern seen in no other gene (2).…”
Section: Introductionmentioning
confidence: 99%